2015
DOI: 10.3390/md13031267
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated Chitosan Oligosaccharides Act as Antagonists against Glutamate-Induced PC12 Cell Death via Bcl-2/Bax Signal Pathway

Abstract: Chitosan oligosaccharides (COSs), depolymerized products of chitosan composed of β-(1→4) d-glucosamine units, have broad range of biological activities such as antitumour, antifungal, and antioxidant activities. In this study, peracetylated chitosan oligosaccharides (PACOs) and N-acetylated chitosan oligosaccharides (NACOs) were prepared from the COSs by chemcal modification. The structures of these monomers were identified using NMR and ESI-MS spectra. Their antagonist effects against glutamate-induced PC12 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Wu et al reported that COS and their derivatives may be able to inhibit apoptosis of neuronal cells in brain cells [ 39 ]. Hao et al discovered that PC12 cells pretreated with per-acetylated chitosan oligosaccharides significantly inhibited glutamate-induced cell apoptosis through regulating elevation of the Bax/Bcl-2 ratio and activation of caspase-3 [ 40 ]. Moreover, water-soluble chitosan with high molecular weights could protect against cell apoptosis induced by serum starvation in human astrocytes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al reported that COS and their derivatives may be able to inhibit apoptosis of neuronal cells in brain cells [ 39 ]. Hao et al discovered that PC12 cells pretreated with per-acetylated chitosan oligosaccharides significantly inhibited glutamate-induced cell apoptosis through regulating elevation of the Bax/Bcl-2 ratio and activation of caspase-3 [ 40 ]. Moreover, water-soluble chitosan with high molecular weights could protect against cell apoptosis induced by serum starvation in human astrocytes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there was no significant change in the gene expression of Bcl‐2 (anti‐apoptosis gene). Hao et al also reported that Bax was significantly inhibited, but there was no change in Bcl‐2 expression after chitosan oligosaccharide treatment in a glutamate‐induced cell death model in a PC12 cell line . Therefore, it is possible that cells related to the allergic response undergo apoptosis more frequently due to upregulation of pro‐apoptotic gene.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2/Bax jointly acts on the outer membrane of the mitochondria, and the ratio between these affects the apoptosis or survival of cells. 10 The overexpression of Bax can antagonize the protective effect of Bcl-2, and induce cell death. The overexpression of Bcl-xL can be found in many tumors; hence, the inhibition of the overexpression of Bcl-2 and Bcl-xL and other antiapoptotic proteins, as well as the recovery of their apoptosis pathway signals and protein expression, are strategies and directions of tumor treatment that are currently to some extent.…”
Section: Discussionmentioning
confidence: 99%